Change of electrical resistivity during phase transitions in NiMnSn-based shape memory alloy - Dagdelen, F.; Ozay, C.; Ercan, E.; Emir, G.; Qader, I. N. (Springer, 2022)
The electrical conductivity is an important behavior of shape memory alloys. It is known that such alloys exhibit different electrical characteristics during phase transformation. In this study, Ni((50-x))Mn39Sn(11)Ta(x) (x = 0, 1, 3) was produced by the arc-melting method under atmosphere control. The phase transformation temperature of these samples was determined by DSC (differential scanning calorimetry) and ER (electrical resistivity) methods. It was found that NiMnSn SMA is a high-temperature shape memory alloy, and the addition of Ta significantly decreased phase transformation temperature of NiMnSn-based SMAs. Besides, it was observed that these alloys exhibited higher resistivity in the martensite phase compared to the austenite phase. The XRD and SEM-EDX were utilized to investigate crystal structure and microstructure of the alloys. Orthorhombic martensite (10 M and 4O) phase picks were found in XRD analysis. In the SEM analysis, on the other hand, grain boundaries, martensite plates, and porous were observed in the samples.
Keywords: NiMnSnTa; Shape memory alloy; Electrical resistivity; Martensite phase